MENYIBAK PRAKTIK KECURANGAN AKUNTANSI DI PT XYZ - - Hariri; Moh. Nizarul Alim (JAFFA, 2015)
This research aims to analyze the practice of accounting fraud to the financial statements XYZ, PT in the period 2010-2013. Based on the results of the analysis indicate that the balance of the financial statements of the period 2010-2013 has made a practice of management accounting fraud to achieve its goals. In the financial statement net income (loss) in 2010 and 2012 accounting fraud management practices to minimize the burden of income tax, whereas in 2011 and 2013 accounting fraud management practice to get the job project tender. Factor in the business of cheating is corruption (bribery), a lot of damage to the business as a result of the rampant practice of bribery in government procurement.The author suggests the regulation (tax office) and public accounting firms, namely that the regulators (Tax Office) conducted a review / inspection directly on the company's assets that has been recorded in the financial statements and the external auditor who has been appointed to conduct an examination of the financial statements is being independent and make the detection of the financial statements.